Lipid Isolated from a Leishmania donovani Strain Reduces Escherichia coli Induced Sepsis in Mice through Inhibition of Inflammatory Responses - Subhadip Das; Nabanita Chatterjee; Dipayan Bose; Somenath Banerjee; Prajnamoy Pal; Tarun Jha; Krishna Das Saha (Hindawi Limited, 2014)
Sepsis is the reflection of systemic immune response that manifests in the sequential inflammatory process in presence of infection. This may occur as a result of gram-negative bacterial sepsis including Escherichia coli infection that gives rise to excessive production of inflammatory mediators and causes severe tissue injuries. We have reported earlier that the lipid of attenuated Leishmania donovani suppresses the inflammatory responses in arthritis patients. Using heat killed E. coli stimulated macrophages, we have now investigated the effect of leishmanial total lipid (LTL) isolated from Leishmania donovani (MHO/IN/1978/UR6) for amelioration of the inflammatory mediators and transcriptional factor with suppression of TLR4-CD14 expression. To evaluate the in vivo effect, E. coli induced murine sepsis model was used focusing on the changes in different parameter(s) of lung injury caused by sepsis, namely, edema, vascular permeability, and pathophysiology, and the status of different cytokine-chemokine(s) and adhesion molecule(s). Due to the effect of LTL, E. coli induced inflammatory cytokine-chemokine(s) levels were significantly reduced in serum and bronchoalveolar lavage fluid simultaneously. LTL also improved the lung injury and suppressed the cell adhesion molecules in lung tissue. These findings indicate that LTL may prove to be a potential anti-inflammatory agent and provide protection against gram-negative bacterial sepsis with pulmonary impairment.